Understanding the Physiological Requirements of the Mountain Bike Cross-Country Olympic Race Format - Hays, Arnaud; Devys, Simon; Bertin, Denis; Marquet, Laurie-anne; Brisswalter, Jeanick (Frontiers in Physiology, 2018)
Objectives: To evaluate the physiological requirements imposed by the current mountain biking Cross-Country Olympic (XCO) format. Methods: 16 Cross-Country cyclists competing at national or international level participated in this study. All participants completed a simulated and a real official race on a cycling-accredited race track. Oxygen consumption (V̇O2) and heart rate (HR) values expressed as %V̇O2max and %HRmax, respectively, were divided into three physiological intensity zones. The first zone (Z1) was the physiological region below VT1, the second zone (Z2) corresponded to a region between VT1 and VT2, and the third zone (Z3) was located between VT2 and VO2max. For power output an additional fourth zone was considered above maximal aerobic power (MAP). Results: When competing in the current XCO format, 37.0±17.9% of the race is performed above the second ventilatory threshold at a mean intensity of 87% V̇O2max and 25% of the race was spent above MAP. This contribution varied between laps, with a very high-intensity during the first lap and more aerobic subsequent laps. Most of the periods beyond MAP oscillated between 5 and 30 seconds. Between these short, repeated bursts, low-intensity periods of exercise were recorded. Conclusion: The current XCO race format is an acyclical and intermittent exercise comparable to high-intensity team sports. Moreover, our results highlight the relevance of V̇O2 values for XCO performance analysis in addition to commonly used HR and/or power output data.